Determination of Correction Value Curve Number (CN) on Watershed With Shape Oval Using HEC HMS Models - Rizal, Nanang Saiful; Farukah, Kus (Proceedings of the International Conference on Green Technology; Vol 8 No 1 (2017): Proceedings of the International Conference on Green TechnologyDO - 10.18860/icgt.v8i1.580, 2017)
Hydrological analysis to obtain surface runoff in watershed (DAS) with oval shape (form factor> 8) often results in large errors (more than 20%) of field observations. This is because the determination of the parameters used the same as the normal watershed without any correction factor. Some influential parameters, including topographic forms of watersheds, land use, soil types, soil moisture. So for the estimation as well as correction of these factors used approach with HEC HMS model. In the HEC HMS model, influencing factors such as soil properties, geological formation and land use have been simplified by the name of the Curve Number (CN) factor. The value of the CN (curve number) varies from 100 (for waterlogged surfaces) to about 30 (for non-watertight surfaces with high infiltration values). The CN factor correction value that will be recommended in this research is yielding the smallest error with the largest correlation coefficient. After performing hydrological analysis by comparing field observation results, the DAS with oval shape was obtained by CN correction number of 1.2, with relative error (11.5%) and correlation coefficient (82%).